Human biliary amount prediction using simple, bile flow-rate corrected and uridine diphosphate glucuronosyltransferase activity corrected allometric methods. (July 2017) - Giri, Poonam; Patel, Harilal; Srinivas, Nuggehally R
Aim: Retrospective scaling of human biliary amounts has been performed using allometry.Methods: Human biliary excretory data for 14 drugs were predicted using simple, bile flow-rate corrected and uridine diphosphate glucuronosyltransferase (UDPGT) activity corrected allometry methods. Allometry was performed using Y = aX b relationship with correction factors. Statistical tests consisting of fold difference (predicted/observed) and root-mean-square error (RMSE) computation were carried out.Results: UDPGT activity corrected allometry predicted higher biliary amounts in humans as compared with other methods. The RMSE values were 38, 32 and 81 for simple, bile flow-rate corrected and UDPGT activity corrected allometry, respectively.Conclusion: Although data showed the usefulness of the approaches for human biliary predictions in the decision process for nominating drug candidate(s) based on % RMSE and fold differences, for some drugs prediction appeared not satisfactory using any of the methods.